A Cauchy problem of parabolic equations with time-dependent coefficients. Issue 6 (26th April 2021) - Liu, Bingchen; Lin, Hongyan; Li, Fengjie
ABSTRACT: In this paper, we study a Cauchy problem of parabolic equations with time-dependent coefficients. The critical Fujita exponents are determined by the exponents of components and dimension of domain and the coefficients. Moreover, we give the optimal classification of blow-up solutions which discriminates simultaneous and non-simultaneous blow-up of two components. At last, simultaneous blow-up rates are obtained.